Network Biology Approaches in Ophthalmological Diseases: A Case Study of Glaucoma - Choudhari, Jyoti Kant; Chatterjee, Tanushree; Gupta, Shailendra; Garcia-Garcia, Jose G.; Vera González, Julio (Systems Medicine - Integrative, Qualitative and Computational Approaches, 2020)
Glaucoma is an eye disease characterized by progressive damage to the optic nerve, often associated to high intraocular pressure, which causes vision impairment and vision loss in long term at the terminal phase. Glaucoma is a multifactorial disease because polymorphisms and deregulation of multiple genes are involved in the onset and development of the disease. However, deregulated genes do not act in isolation but are integrated into large networks of molecular entities. Systems and network biology are emerging disciplines in biomedicine in which mathematical modeling and computational biology tools are employed to integrate and analyze high-throughput quantitative biological data. In this article we discuss how these two new methodologies can be used to reconstruct the networks of deregulated genes behind glaucoma, networks that can be used to obtain mechanistic insights about the pathogenesis of the disease, and eventually to design molecular evidence-based therapies.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Angle closure glaucoma (ACG); Bioinformatics; Intraocular pressure (IOP); Network biology; Personalized medicine; Primary congenital glaucoma (PCG); Primary normal-tension glaucoma (NTG); Primary open angle glaucoma (POAG); Systems biology; Systems medicine